2009
DOI: 10.1353/jef.0.0012
|View full text |Cite
|
Sign up to set email alerts
|

Examining Economies of Scale in School Consolidation: Assessment of Indiana School Districts

Abstract: This article examines the potential for reducing costs through school district consolidation by employing economies of scale. Utilizing Indiana school district data primarily from 2004 through 2006, we find evidence for scale economies with optimal enrollment being 1,942 students, with a per pupil estimated cost at $9,414. The 95% confidence interval of the optimal enrollment is 1,300 to 2,903 students. The study examines several hypotheses discussed in this line of literature. Transportation does not appear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…School district consolidations often are proposed as a mechanism to realize fiscal savings for local communities; indeed, the number of U.S. school districts has declined dramatically over the past 70 years, decreasing from 117,108 in 1939-40 to 13,809 in 2008(Snyder and Dillow 2010. Consolidations may occur to promote fiscal and administrative efficiency, or as a result of significant enrollment declines, diminished real estate valuations, and limited availability of highly qualified teachers (Howley, Johnson, and Petrie 2011;Zimmer, DeBoer, and Hirth 2009). Research primarily has focused on perceived benefits and disadvantages of consolidations and superintendents' political roles in negotiating through consolidation conversations within the impacted communities (Alsbury and Shaw 2005).…”
Section: Leading the Newly Consolidated High School: Exciting Opportumentioning
confidence: 99%
See 1 more Smart Citation
“…School district consolidations often are proposed as a mechanism to realize fiscal savings for local communities; indeed, the number of U.S. school districts has declined dramatically over the past 70 years, decreasing from 117,108 in 1939-40 to 13,809 in 2008(Snyder and Dillow 2010. Consolidations may occur to promote fiscal and administrative efficiency, or as a result of significant enrollment declines, diminished real estate valuations, and limited availability of highly qualified teachers (Howley, Johnson, and Petrie 2011;Zimmer, DeBoer, and Hirth 2009). Research primarily has focused on perceived benefits and disadvantages of consolidations and superintendents' political roles in negotiating through consolidation conversations within the impacted communities (Alsbury and Shaw 2005).…”
Section: Leading the Newly Consolidated High School: Exciting Opportumentioning
confidence: 99%
“…Consolidation often "inhibits the spread of cultural knowledge and exacerbates a community's social and economic problems" (Nitta, Holley, and Wrobel 2010, 3). Opponents cite negative consequences for students, such as longer bus rides and larger class sizes (Alsbury and Thomas 2008;Zimmer, DeBoer, and Hirth 2009). Other concerns relate to perceived reduction in community representation on the board of education (Alsbury and Thomas 2008), and parent participation (Howley, Johnson, and Petrie 2011;Nitta, Holley, and Wrobel 2010).…”
Section: School District Consolidationmentioning
confidence: 99%
“…However, small school reform and school district consolidation continues in sections of the Midwest. States such as Illinois, South Dakota, and Indiana have provided incentives to promote school district consolidation (Zimmer, DeBoer, & Hirth, 2009). Indiana recommended consolidation of districts with less than 2,000 students and offered grants to districts interested in merging.…”
Section: Chapter 2: Literature Reviewmentioning
confidence: 99%
“…To inform policy and the public, Zimmer et al (2009) (Duncombe et al, 1996;Duncombe & Yinger, 2007). The Indiana study indicated economies of scale were optimal at an enrollment of 1,942 students, with a 95% confidence interval spanning from 1,300 to 2,903 students (Zimmer et al, 2009).…”
Section: Chapter 2: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation